Fully plasma-based electron injector for a linear collider or XFEL - T. N. Dalichaouch; X. L. Xu; F. Li; F. S. Tsung; W. B. Mori (Physical Review Research)
We demonstrate through high-fidelity particle-in-cell (PIC) simulations a simple approach for efficiently generating 20+ GeV electron beams with the necessary charge, energy spread, and emittance for use as an injector in a future linear collider or a next generation XFEL. A high quality injected bunch is generated by self-focusing an unmatched electron driver in a nonlinear plasma wakefield. Over pump depletion distances, the drive beam dynamics and self-loading effects lead to high energy, low-energy spread output beams. For plasma densities of 10^{18}cm^{−3}, PIC simulation results indicate that self-injected beams with 0.52nC charge can be accelerated to 20 GeV with projected core energy spreads of ≲1%, normalized slice emittances of 110nm, peak normalized brightness of ≳10^{19}A/m^{2}/rad^{2}, and transfer efficiencies of ≳44%.